Socio-economic factors of patients of a military sanatorium in Krynica Zdrój and selected elements of their lifestyle - Zwolińska-Mirek, Katarzyna; Mirek, Janusz; Cygnar, Elżbieta; Proszowska, Jolanta (Health Promotion & Physical Activity, 2019)
Introduction: One of the crucial factors influencing the lifestyle and health-related behaviors undertaken by people is their social and economic situation. Apart from material status, the level of education plays a significant role. Social and economic factors are major determinants influencing population health. The socio-economic situation may significantly affect the health-related behaviors undertaken in the group in question. The paper attempts to assess the impact of the socio-economic background of patients with mobility dysfunctions and comorbidities, undergoing the spa and rehabilitation treatment on their health-related behaviors. The study was supposed to answer the question whether undertaking health-related behaviors is dependent on the socio-economic factors of the patients in the study. The study constitutes only one of the elements of broader analysis of health-related behaviors covering patients undergoing sanatorium treatment. Material and methods: The group included in the study consisted of 450 patients (300 women and 150 men) undergoing spa and rehabilitation treatment at the 20 Military Spa and Rehabilitation Hospital in Krynica-Zdrój. Patients were referred to sanatorium treatment mainly due to mobility dysfunctions but also due to comorbidities. Diagnostic survey was used as a research method and the author’s own questionnaire specifically designed for its purpose was applied. The questions concerned physical activity, nutrition, use of psychoactive substances and preventive examinations. The analysis of the patients’ medical documentation provided the authors with objective information about the results of laboratory tests, current health problems and ailments as well as the course of the applied treatment. Research and conclusions: The education level together with economic status of the respondents have a statistically significant impact on the form of selected physical activity in the group under study. Patients with average income went for walks more often while remedial gymnastics was often practiced by patients with monthly net income above PLN 1.500. No statistically significant correlations between the education level and economic status of the patients and the regularity of meals as well as the number of hours devoted to sleep was stated. The correlation between the frequency of stays in sanatorium and the place of residence, education level, type of work performed as well as wealth level was not found.